Teachers’ professional reasoning about their pedagogical use of technology - Heitink, M.; Voogt, J.; Verplanken, L.; van Braak, J.; Fisser, P. (Computers and education, 2016)
This study focused on teachers’ reasoning about the use of technology in practice. Both teachers’ professional reasoning and their technology use were investigated. Through video cases, 157 teachers demonstrated their technology use in practice and commented on the reasoning behind their actions. Results show that most technology use was intended to strengthen both pedagogy and subject matter, or else pedagogy alone. Reasons addressed making learning attractive for students, realizing educational goals and facilitating the learning process. The majority of teachers’ technology use in practice shows aspects of the knowledge transfer model of teaching. Most technology tools were used to support a learning activity; the use of technology was essential in only a few video cases. About half of the video cases showed alignment between reasoning and practice. The results contribute to better understanding of how teachers reason professionally about their technology use. •Teachers (n = 157) demonstrate technology use and discuss their reasoning.•Reasons address attractiveness, learning goals and learning processes.•The majority of teachers use technology to support knowledge transfer.•Teachers demonstrate integration of technology, pedagogy and content.•About half of the teachers show alignment between their reasoning and practice.